Microcirculatory disturbances – relationship with peripheral vascular reactivity and structure-functional properties of endothelium in systemic sclerosis - U Y Ruzentsova (Научно-практическая ревматология, 2009)
Microcirculatory disturbances – relationship with peripheral vascular reactivity and structure- functional properties of endothelium in systemic sclerosis. Objective. To assess basal capillary blood flow and examine degree of microcirculatory disturbances depending on plasma endothelin 1 content and structure-functional status of endothelium in pts with systemic sclerosis (SS). Material and methods. 31 pts with SS (31 female and 3 male) with mean age 48±2,1 years and disease duration 9,9±1,3 years and 15 healthy persons match on age and sex were included. Laser Doppler flowmetry, assessment of plasma endothelin-1 (ET1), peripheral blood circulating endothelial cells (CEC), endothelium-dependent (EDVD) and endothelium-independent vasodilatation (EIVD) was performed. Results. All pts with SS had decrease of capillary perfusion and disturbance of peripheral vessel reactivity in comparison with healthy persons. Microcirculatory disorders intensity in SS was shown to depend on plasma ET1 level. Basal values of ET1 concentration were significantly higher in comparison with control group. Peripheral microcirculation measures tightly correlated with plasma ET1 and CEC what point to systemic character of capillary blood flow disturbances in SS. Conclusion. Microcirculatory disorders intensity in SS depends on degree of structure-functional endothelium changes on peripheral and systemic vessel levels.